A prognostic model predicted deterioration in health-related quality of life in older patients with multimorbidity and polypharmacy - González-González, AI; Meid, AD; Dinh, TS; Blom, JW; van den Akker, M; Elders, PJM; Thiem, U; De Gaudry, DK; Swart, KMA; Rudolf, H; Bosch-Lenders, D; Trampisch, H-J; et al. (Elsevier, 2020)
Objectives: To develop and validate a prognostic model to predict deterioration in health-related quality of life (dHRQoL) in older general practice patients with at least one chronic condition and one chronic prescription.